2012
DOI: 10.3390/cryst2031067
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Phase Transition in Strongly Electron-Lattice and Electron–Electron Correlated Molecular Crystals

Abstract: Strongly electron-lattice-and electron-electron-correlated molecular crystals, such as charge transfer (CT) complexes, are often sensitive to external stimuli, e.g., photoexcitation, due to the cooperative or competitive correlation of various interactions present in the crystals. These crystals are thus productive targets for studying photoinduced phase transitions (PIPTs). Recent advancements in research on the PIPT of CT complexes, especially Et 2 Me 2 Sb[Pd(dmit) 2 ] 2 and (EDO-TTF) 2 PF 6 , are reviewed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Among the materials exhibiting PIPT, we have intensively studied organic charge transfer (CT) complexes . CT complexes are single crystals consisting of small π-electron molecules and exhibit a wide variety of phases, such as metal, charge-ordered insulator, Mott insulator, and superconductor, by applying weak external stimuli, because they are essentially strongly correlated electron systems. Moreover, CT complexes are suitable for applying time-resolved vibrational spectroscopy because their constituent molecules include the CC stretching vibrational modes whose energies and intensities are sensitive to the structure and charge of the molecules. We have found that approximately 100 ps are required for the emergence of the high-temperature phase in some types of CT complexes. ,,, To elucidate the origin of this slow emergence of the high-temperature phase, it is useful to compare two samples that have the same characteristics except for one distinction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the materials exhibiting PIPT, we have intensively studied organic charge transfer (CT) complexes . CT complexes are single crystals consisting of small π-electron molecules and exhibit a wide variety of phases, such as metal, charge-ordered insulator, Mott insulator, and superconductor, by applying weak external stimuli, because they are essentially strongly correlated electron systems. Moreover, CT complexes are suitable for applying time-resolved vibrational spectroscopy because their constituent molecules include the CC stretching vibrational modes whose energies and intensities are sensitive to the structure and charge of the molecules. We have found that approximately 100 ps are required for the emergence of the high-temperature phase in some types of CT complexes. ,,, To elucidate the origin of this slow emergence of the high-temperature phase, it is useful to compare two samples that have the same characteristics except for one distinction.…”
Section: Introductionmentioning
confidence: 99%
“…16−19 Among the materials exhibiting PIPT, we have intensively studied organic charge transfer (CT) complexes. 22 CT complexes are single crystals consisting of small π-electron molecules and exhibit a wide variety of phases, such as metal, charge-ordered insulator, Mott insulator, and superconductor, by applying weak external stimuli, because they are essentially strongly correlated electron systems. 23−28 Moreover, CT complexes are suitable for applying time-resolved vibrational spectroscopy because their constituent molecules include the CC stretching vibrational modes whose energies and intensities are sensitive to the structure and charge of the molecules.…”
Section: Introductionmentioning
confidence: 99%